2016
DOI: 10.1111/socf.12272
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Inequality and Carbon Emissions in Comparative Perspective

Abstract: Drawing from multiple bodies of literature, the authors investigate the relationship between consumptionbased carbon emissions and domestic income inequality for 67 nations from 1991 to 2008. Results of twoway fixed-effects longitudinal models indicate that the relationship between national-level emissions and inequality changes through time and varies for nations in different macroeconomic contexts. For high-income nations, the relationship shifts from negative to positive, suggesting that in recent years, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 66 publications
4
72
0
Order By: Relevance
“…Jorgenson et al (2016) find that among a sample of high-income nations, income inequality has a positive effect on national-level emissions, while for a sample of low income nations, the association between income inequality and emissions is nonsignificant. Results from a study by Knight, Schor and Jorgenson (2017) similarly show that among a sample of high income nations, wealth inequality is positively associated with national-level emissions.…”
Section: Brief Literature Reviewmentioning
confidence: 70%
See 1 more Smart Citation
“…Jorgenson et al (2016) find that among a sample of high-income nations, income inequality has a positive effect on national-level emissions, while for a sample of low income nations, the association between income inequality and emissions is nonsignificant. Results from a study by Knight, Schor and Jorgenson (2017) similarly show that among a sample of high income nations, wealth inequality is positively associated with national-level emissions.…”
Section: Brief Literature Reviewmentioning
confidence: 70%
“…An emerging area of research attempts to increase our collective understanding of the complexities of inequality and climate change by focusing on how levels of income inequality within nations might be associated with levels of anthropogenic carbon emis-sions (e.g., Jorgenson et al 2016;Knight, Schor and Jorgenson 2017). If it is found that income inequality is associated with higher levels of emissions, carefully planned strategies and initiatives to reduce income inequality could result in climate change mitigation, in addition to other associated social and environmental benefits (Wilkinson and Pickett 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These associations are observed within more economically developed nations, such as the United States (Jorgenson, Schor, et al 2016;Jorgenson, Schor et al 2017;Knight et al 2017) and in developing nations as well (Hubacek et al 2017a).…”
Section: Power Social Stratification and Inequalitymentioning
confidence: 83%
“…And my recent collaborative research on income and wealth inequality and carbon emissions, including work published in Sociological Forum (Jorgenson et al. ), was featured in an “Outlook” article that was commissioned by Nature (Eisenstein ) that focuses on the role of social science in climate policy and the importance in developing strategies to ensure that the needs of the few do not outweigh those of the rest. For this, I was contacted by the author of the article for Nature , who asked me a series of questions about the inequality and emissions research and the role of social science in climate policy.…”
Section: Publishing Tacticsmentioning
confidence: 99%